Empowering legislatures: the politics of legislative veto oversight among the U.S. states. Issue 3 (3rd July 2021) - Berry, Michael
ABSTRACT: State legislatures in the United States began using the legislative veto in 1939 to block rules issued by state agencies. At present, 25 state legislatures possess some form of independent legislative veto authority. This study uses a transaction cost theoretical approach to analyse factors expected to influence the adoption and expansion of legislative veto oversight. Results indicate that such measures are more likely in non-Southern states when a single party controls the state legislature, while legislative size and professionalisation do not substantially affect legislative veto reforms. Empirical analysis differentiating veto power according to whether legislators can nullify or suspend rules shows some differences in the factors affecting the imposition of each oversight type. The most consistent finding is that empowering legislatures with legislative veto authority is more likely to occur with a Republican governor in office.